Mine-site derived particulate matter exposure exacerbates neurological and pulmonary inflammatory outcomes in an autoimmune mouse model. Issue 12 (18th June 2021) - Wilson, Alexis; Velasco, Carmen A.; Herbert, Guy W.; Lucas, Selita N.; Sanchez, Bethany N.; Cerrato, José M.; Spilde, Michael; Li, Quan-Zhen; Campen, Matthew J.; Zychowski, Katherine E.
ABSTRACT: The Southwestern United States has a legacy of industrial mining due to the presence of rich mineral ore deposits. The relationship between environmental inhaled particulate matter (PM) exposures and neurological outcomes within an autoimmune context is understudied. The aim of this study was to compare two regionally-relevant dusts from high-priority abandoned mine-sites, Claim 28 PM, from Blue Gap Tachee, AZ and St. Anthony mine PM, from the Pueblo of Laguna, NM and to expose autoimmune-prone mice (NZBWF1/J). Mice were randomly assigned to one of three groups (n = 8/group): DM (dispersion media, control), Claim 28 PM, or St. Anthony PM, subjected to oropharyngeal aspiration of (100 µg/50 µl), once per week for a total of 4 consecutive doses. A battery of immunological and neurological endpoints was assessed at 24 weeks of age including: bronchoalveolar lavage cell counts, lung gene expression, brain immunohistochemistry, behavioral tasks and serum autoimmune biomarkers. Bronchoalveolar lavage results demonstrated a significant increase in number of polymorphonuclear neutrophils following Claim 28 and St. Anthony mine PM aspiration. Lung mRNA expression showed significant upregulation in CCL-2 and IL-1ß following St. Anthony mine PM aspiration. In addition, neuroinflammation was present in both Claim 28 and St. Anthony mine-site derived PM exposure groups. Behavioral tasks resulted in significant deficits as determined by Y-maze new arm frequency following Claim 28 aspiration. Neutrophil elastase was significantly upregulated in the St. Anthony mine exposure group. Interestingly, there were no significant changes in serum autoantigens suggesting systemic inflammatory effects may be mediated through other molecular mechanisms following low-dose PM exposures.